Cover Picture: Double‐Stranded Helical Oligomers Covalently Bridged by Rotary Cyclic Boronate Esters (Chem. Asian J. 8/2017). Issue 8 (28th March 2017) - Iida, Hiroki; Ohmura, Kenji; Noda, Ryuta; Iwahana, Soichiro; Katagiri, Hiroshi; Ousaka, Naoki; Hayashi, Taku; Hijikata, Yuh; Irle, Stephan; Yashima, Eiji
Abstract : Setting the helices in motion : The design and construction of artificial molecular rotors that perform a sophisticated rotary motion have attracted considerable interest in the context of molecular machines. In this study, novel double‐stranded helices covalently bridged by two cyclic boronate esters were prepared via simple mixing of two complementary dimer strands bearing diethyl boronates and diols. A rotational motion of the encased cyclic boronate ester units can take place simultaneously with helix‐inversion of the double‐stranded helical framework, thus providing a unique molecular rotor that undergoes dual rotary and inverting (twisting) motions. More information can be found in the Full Paper by Hiroki Iida, Eiji Yashima, Stephan Irle et al. onpage 927 in Issue 8, 2017 (DOI:10.1002/asia.201700162 ).